Custos com suplementação alimentar na bovinocultura de leite - Toigo, Cleber (2014)
The present study aimed to analyze the economic feasibility of production of milk with the use of dietary supplements in the diet. Took the approach of some assumptions related to competitiveness in dairy production, costs of production, possible alternative foods that can be used in the diet. Through questionnaires, economic and financial information were collected in 22 (twenty two) stores the Southwest of Paraná, and western Santa Catarina. Grande those producers is part of the family farm, which features small properties. Supplementation is present in all properties, with almost all respondents producers use the same ingredients in the diet. Silage, concentrate and mineral salt supplements are the most used on the farms. With respect to cost, silage and concentrate were the ingredients that had higher purchasing costs and / or production. However supplements are of great importance during critical periods for silage, and the concentrate to increase production and maintenance of the cow. It is concluded that dietary supplementation is essential for milk production, but the creator must be aware of the production costs, and represent the largest portion of the total costs of dairy cattle.